Shaoshia, an unusual new cicada genus from Pakistan with the description of a new species (Hemiptera: Cicadidae) - Wei, Cong; Ahmed, Zubair; Rizvi, Syed Anser (Zootaxa, 2010)
Shaoshia zhangi gen. & sp. n., from Pakistan, is described and placed in the cicada tribe Cicadatrini. The new genus is characterized by its completely hyaline wings with seven apical cells in the forewing and four apical cells in the hind wing, which is unique among Cicadidae. The relationship between the new genus and other taxa is discussed.